Necessidades formativas de professores que atuam nos espaços de privação de liberdade em Cuiabá e Várzea Grande-MT - Moraes, Luciana Ferreira da Silva (2019)
The educational actions developed by professionals of Basic Education of the state schools of Mato Grosso take place in the school spaces through a study project elaborated “from a situational diagnosis with the use of techniques and resources that point out the potentialities, needs and difficulties of students within learning and teaching process” (SEDUC, 2018, p. 2).Whereas this context, this study aims to analyze the teacher education needs who work in classrooms in the prison unities of Cuiabá and Várzea Grande-MT. In order to achieve the proposed objective, this study seeks to answer the following question: Which educational needs emerge in the processes of experiences and in the teachers’ sayings who work in classrooms in the prison unities of Cuiabá and Várzea Grande-MT? This is a qualitative approach study, developed based on field research. For data collection, the following techniques were used: participant observation in the weekly educational meetings of the Teacher Education Program at School and also conducting narrative interviews. The treatment of the obtained data was done through the content analysis proposed by Bardin (2016).The study collaborators are: the teacher educator responsible for accompaniment to educational meetings of Teacher Education Program at School and the teachers involved in this educational event. With this study, based on Paulo Freire’s Liberating Pedagogy, it was found that teachers present collective, contextual and individual educational needs. The collective educational needs, at mostly, come from the context where it was developed the educational practice. From this, it emerges the main challenge and, in the same time, it was arranged as a collective educational need: articulation between theory and practice. In addition, there are contextual educational needs where come from spaces of deprivation of liberty, an environment marked by rules, disciplines and apart students, for a period of time, from social interaction. Lastly, the analysis of the set of data showed that teachers are in stages of distinct career, have a variety of academic education, singular histories of personal and professional life and these aspects point to individual educational needs referred to their education, work and concerned area. The variety of educational needs identified demonstrate the relevance of (re)thinking about Continuing Educational of these teachers who work on education at prison.